In Vivo Antiplasmodial Activity of Terminalia mantaly Stem Bark Aqueous Extract in Mice Infected by Plasmodium berghei - Mariscal Brice Tchatat Tali; Cedric Derick Jiatsa Mbouna; Lauve Rachel Yamthe Tchokouaha; Patrick Valere Tsouh Fokou; Jaures Marius Tsakem Nangap; Rodrigue Keumoe; Alvine Ngoutane Mfopa; Issakou Bakarnga-via; Raceline Gounoue Kamkumo; Fabrice Fekam Boyom (Journal of Parasitology Research)
Background. Terminalia mantaly is used in Cameroon traditional medicine to treat malaria and related symptoms. However, its antiplasmodial efficacy is still to be established. Objectives. The present study is aimed at evaluating the in vitro and in vivo antiplasmodial activity and the oral acute toxicity of the Terminalia mantaly extracts. Materials and Methods. Extracts were prepared from leaves and stem bark of T. mantaly, by maceration in distilled water, methanol, ethanol, dichloromethane (DCM), and hexane. All extracts were initially screened in vitro against the chloroquine-resistant strain W2 of P. falciparum to confirm its in vitro activity, and the most potent one was assessed in malaria mouse model at three concentrations (100, 200, and 400 mg/kg/bw). Biochemical, hematological, and histological parameters were also determined. Results. Overall, 7 extracts showed in vitro antiplasmodial activity with IC50 ranging from 0.809 μg/mL to 5.886 μg/mL. The aqueous extract from the stem bark of T. mantaly (Tmsbw) was the most potent (IC50=0.809 μg/mL) and was further assessed for acute toxicity and efficacy in Plasmodium berghei-infected mice. Tmsbw was safe in mice with a median lethal dose (LD50) higher than 2000 mg/kg of body weight. It also exerted a good antimalarial efficacy in vivo with ED50 of 69.50 mg/kg and had no significant effect on biochemical, hematological, and histological parameters. Conclusion. The results suggest that the stem bark extract of T. mantaly possesses antimalarial activity.